Organization of health and hygiene measures in prisons in Bosnia and Herzegovina - Alispahić, Bakir; Hadzikadunić, Admir; Deko, Amra (Technium Social Sciences Journal, 2021)
Persons deprived of their liberty are punished by the mere fact that they have been deprived of their liberty, so the conditions in which they find themselves must not further increase their suffering. In order to protect the human dignity of persons deprived of their liberty, it is necessary to allow them to exercise their human rights, among which the right to adequate health and hygiene protection occupies a significant place, which increases the chance for successful resocialization and reintegration. The subject of this paper is the organization of health and hygiene programs in the prison system in Bosnia and Herzegovina (case study of the Sarajevo Penal-Correctional Institution). The research also examines the access to medical doctors, medication, medical equipment and instruments, the condition of outpatient clinics, keeping records of the health status of convicts, the need to develop a strategy to provide assistance to people with drug problems and systematic testing for infectious diseases. The aim of this paper is to shed light on the general attitude towards persons deprived of their liberty, consequently, the care provided to them in prison units, and to point out the shortcomings. Also, the aim of this paper is to provide insight into the health and hygiene protection measures for prisoners.